Switching on the light: using metagenomic shotgun sequencing to characterize the intestinal microbiome of Atlantic cod - Even Sannes Riiser; Thomas H.A. Haverkamp; Srinidhi Varadharajan; Ørnulf Borgan; Kjetill S. Jakobsen; Sissel Jentoft; Bastiaan Star (Environmental Microbiology, 2019)
Summary Atlantic cod ( Gadus morhua ) is an ecologically important species with a wide‐spread distribution in the North Atlantic Ocean, yet little is known about the diversity of its intestinal microbiome in its natural habitat. No geographical differentiation in this microbiome was observed based on 16S rRNA amplicon analyses, yet such finding may result from an inherent lack of power of this method to resolve fine‐scaled biological complexity. Here, we use metagenomic shotgun sequencing to investigate the intestinal microbiome of 19 adult Atlantic cod individuals from two coastal populations in Norway–located 470 km apart. Resolving the species community to unprecedented resolution, we identify two abundant species, Photobacterium iliopiscarium and Photobacterium kishitanii , which comprise over 50% of the classified reads. Interestingly, the intestinal P. kishitanii strains have functionally intact lux genes, and its high abundance suggests that fish intestines form an important part of its ecological niche. These observations support a hypothesis that bioluminescence plays an ecological role in the marine food web. Despite our improved taxonomical resolution, we identify no geographical differences in bacterial community structure, indicating that the intestinal microbiome of these coastal cod is colonized by a limited number of closely related bacterial species with a broad geographical distribution.